Altmetrics and social network analysis of economics, econometrics and finance research: The case study of turkey - (:unkn) unknown (National Institute of Science Communication and Information Resources, 2021)
Increase in the use of social media has enabled academic studies to be spoken and shared on these platforms. With the widespread use of these networks, concepts such as the number of shares, as well as the number of citations have been among the conspicuous determinants on the visibility, popularity or even usefulness of research works. In this study, Mendeley reader activities and features of 1560 articles that were written by Turkish authors in the field of Economics, Econometrics and Finance between 2016-2018 in Scopus were analysed. By calculating the correlation between citations and Mendeley readership counts, it has been investigated whether Mendeley reader statistics are able to be evaluated as an alternative metric for citations. International cooperation with social network analysis was also evaluated. According to Mendeley results, the articles have a wide audience from various disciplines and different statuses. Correlation between citations and readership counts was statistically significant. When network structure is evaluated, international cooperation has become more concentrated over the years. © 2021, National Institute of Science Communication and Information Resources. All rights reserved.
Keywords: Altmetrics; Mendeley; Readership Analysis; Social Network Analysis